Pyrometallurgical treatment of jarosite residue with a mixture of CaO, SiO2, and CaSi - Antonio Romero-Serrano; Cancio Jiménez-Lugos; Manuel Flores-Favela; Aurelio Hernández-Ramírez; Josué López-Rodríguez; Alejandro Cruz-Ramírez; Eduardo Colín-García (Journal of Mining and Metallurgy, Section B: Metallurgy, 2024)
During the electrolytical production of zinc, iron in solutions is mainly controlled by the precipitation of jarosite. This precipitate also contains valuable metals (Zn, Pb, Cu, Ag) and toxic elements (Hg, Cd, As). This study deals with the pyrometallurgical treatment of jarosite waste to recover metal values and convert the waste into environmentally acceptable slag. Initially, the sample was heated to 100 °C to remove moisture, then roasted at 700 °C to release some OH‒ and sulfate groups by thermal decomposition. The analysis of the ternary diagram SiO2-CaO-Fe2O3 phase diagram showed that a flux with 48% CaO and 52% SiO2 can be used to melt the roasted jarosite at 1400 °C. Subsequently, tests were carried out with the reducing agent (CaSi), resulting in a mixture of slag and two metallic phases, one a Fe-Si alloy and the other a Pb-rich phase with the valuable metal Ag. Both the metallic and slag phases were characterised by chemical analysis, SEM-EDS and XRD. Additionally, the raw jarosite residue and the final slag were leached with an aqueous acetic acid solution to estimate their chemical stability. The obtained results show that the slag produced after the reduction of jarosite residue meets the environmental specifications and could be used as raw material in other industries.